Yang Naimei - life practice of a chinese “flapper” of women's development in China - Yanrui Xu; Junwei Wang (Trans/Form/Ação)
As one of the earliest movie stars in China, Yang Naimei's life reflects the process of professionalization and modernization of Chinese women in the early 20th century. This study discusses the life practices and significance of Yang Naimei as a Chinese flapper. Flapper refers to the modern girl who arose in Europe and America in the 1920s as a challenge to traditional lifestyles. Yang Naimei fully embodied the characters of the flapper. She often played an unruly woman on the screen, and she had many relationships in her life, accumulating wealth and a reputation with her acting career. However, society at that time did not provide enough space for the sustainable development of the women’s generation, like Yang Naimei, in economic, political and personal life. After the loss of her youth, she was disposed of by the film industry and suffered from poverty and disease in the latter half of her life. Taking Yang Naimei as an illustration of the times can reflect the twists and turns in the treatment of Chinese women offered by the society.